2022
DOI: 10.3389/fphys.2022.885545
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Purinergic P2X7 Receptor Inhibition on Acrolein-Induced Urothelial Cell Damage

Abstract: Patients undergoing chemotherapy with cyclophosphamide experience cystitis due to excretion of a toxic metabolite, acrolein. Cystitis, an inflammation of the bladder, is associated with damage to the integrity of the urothelial barrier. The purinergic P2X7 receptor (P2X7R) is increasingly recognized for its role in inflammation and cell death. P2X7R is expressed abundantly on the bladder urothelium. The aim of this study was to investigate the role of P2X7R in acrolein-induced inflammatory damage in primary cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Further, functional barrier data support the idea that mitochondrial dysfunction, Ca 2+ intracellular and ATP extracellular release underlie BBB injury by ETH or 1.8% e-Cig, and prevention of these negative effects by P2X7r inhibition preserves integrity. A recent study demonstrated that urothelial barrier function was normalized by P2X7r selective antagonist, A804598, in acrolein-induced bladder urothelial cell damage in a porcine model [ 30 ]. The multifaced role of P2X7r in BBB regulation during neuroinflammatory diseases has been recognized [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, functional barrier data support the idea that mitochondrial dysfunction, Ca 2+ intracellular and ATP extracellular release underlie BBB injury by ETH or 1.8% e-Cig, and prevention of these negative effects by P2X7r inhibition preserves integrity. A recent study demonstrated that urothelial barrier function was normalized by P2X7r selective antagonist, A804598, in acrolein-induced bladder urothelial cell damage in a porcine model [ 30 ]. The multifaced role of P2X7r in BBB regulation during neuroinflammatory diseases has been recognized [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this report we treated hBMVECs with A804598 (10 μM), a novel and competitive antagonist of P2X7r that is known to have high affinity for blocking P2X7 receptors [ 29 , 30 ]. Our aim was to identify unifying mechanisms of brain endothelial injury caused by ETH, ALD, and e-Cig vape.…”
Section: Introductionmentioning
confidence: 99%
“…The protocol for measuring trans-epithelial electrical resistance (TEER) was adapted from the one used for TEER measurement in porcine urothelial cells ( Taidi et al, 2022 ). In brief, once MDCK cells in T75 flasks had reached 80% confluence, they were passaged and plated (1 × 10 5 cells per well) onto Corning Transwell inserts and cultured in MEM supplemented with 10% FBS and 1% penicillin streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…In a study of primary cultures of porcine bladder urothelial cells, acrolein-induced inflammatory damage had increased cell toxicity, increased P2X7 expression, and disrupted the tight junction protein ZO-1. However, this effect was abolished with the treatment of the selective P2X7R antagonist A804598, thus retained cell integrity and prevented degradation of tight junctions (Taidi et al, 2022). Similarly, another study reported on porcine theca cells from antral follicles, extracellular ATP induced cell death and DNA fragmentation was mediated by P2X7.…”
Section: P2x7 and Nlrp3 Activation In Porcine Burn Injurymentioning
confidence: 91%